2021
DOI: 10.1007/s10120-021-01264-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of H. pylori fecal antigen test using fecal immunochemical test (FIT)

Abstract: Background Gastric and colorectal cancer (CRC) are both one of the most common cancers worldwide. In many countries fecal immunochemical tests (FIT)-based CRC screening has been implemented. We investigated if FIT can also be applied for detection of H. pylori, the main risk factor for gastric cancer. Methods This prospective study included participants over 18 years of age referred for urea breath test (UBT). Patients were excluded if they had used antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Rt-PCR results were in 100% concordance with culture results from these six patients, with three cases of clarithromycin resistance and three cases of clarithromycin-susceptible H. pylori. 18 In this followup study we show that H. pylori antigen testing in traditional stool and FIT performs equally well for the verification of eradication of H.…”
Section: F I G U R E 2 Visual Representation Of Helicobacter Pylori E...mentioning
confidence: 62%
See 2 more Smart Citations
“…Rt-PCR results were in 100% concordance with culture results from these six patients, with three cases of clarithromycin resistance and three cases of clarithromycin-susceptible H. pylori. 18 In this followup study we show that H. pylori antigen testing in traditional stool and FIT performs equally well for the verification of eradication of H.…”
Section: F I G U R E 2 Visual Representation Of Helicobacter Pylori E...mentioning
confidence: 62%
“…We have previously shown that the non‐invasive stool antigen test (SAT), which detects H. pylori antigen in fecal matter, is as efficient for the diagnosis of H. pylori infection as the urea breath test (UBT). This study also showed that patients are more comfortable collecting fecal immunohistochemical test (FIT) samples than solid fecal material 18 and that fluid collected from FIT tests was equally effective for H. pylori stool antigen detection as solid stool samples.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…SAT has been favored in recent years due to its advantages of convenient operation and independent of expensive equipment 28 . Although the sensitivity and specificity of some commercial products have achieved comparable results to the urea breath test in scientific research, 29–33 there is still a lack of large‐scale population test data to support it. It can only be used as a supplement to the urea breath test at present, and cannot completely replace the breath test.…”
Section: Discussionmentioning
confidence: 99%
“…SAT has been favored in recent years due to its advantages of convenient operation and independent of expensive equipment. 28 Although the sensitivity and specificity of some commercial products have achieved comparable results to the urea breath test in scientific research, [29][30][31][32][33] there is still a lack of large-scale popula- To develop a high-sensitivity, high-specificity stool antigen detection kit, one or several specific antigens that can be used as detection targets must first be screened out. These antigens should have high protein abundance in most or all H. pylori strains, their protein sequences should be conserved in H. pylori, at the same time, the sequence similarity with homologous proteins in other intestinal flora should be low, so as to ensure a wide range of H. pylori strain coverage and the specificity of the detection.…”
Section: Epitope Prediction Of the Dna Starvation/ Stationary Phase P...mentioning
confidence: 99%